Perancangan Aplikasi Kamus Bahasa Batak Menggunakan Metode Searching - Samsir Samsir (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2022)
In modern times like today, of course there are many dictionaries in circulation, ranging from books, desktop, web, and even mobile. And each has its advantages and disadvantages. For example, a conventional dictionary in the form of a book, has advantages in terms of the amount of vocabulary but requires a long time in terms of Word Search, and less practical to carry anywhere. To overcome this, a mobile-based dictionary is the answer. The author designed the batak language dictionary application with the hope of answering the expectations of users who need a practical and responsive dictionary. The dictionary has not been designed using the searching method. Every country even in a narrower scope, today the development of technology has produced several devices, one form of application. The application is a device that can run several features such as a communication medium that is easy to use and easy to understand so that if there are people who want to learn it will be very easy to understand and for people, especially batak blood also if they do not understand their own language by using this application will understand where the shortcomings in the batak language.